2009
DOI: 10.3109/00016480802642096
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for squamous cell carcinoma of the temporal bone: extensive bone involvement or extensive soft tissue involvement?

Abstract: Conclusion:Extensive bone erosion correlated with a worse prognosis of the squamous cell carcinoma (SCC) of the temporal bone but extensive soft tissue involvement did not correlate with prognosis in this study. Resectability of the tumor seems to be major prognostic factors of temporal bone SCC.Objective: Prognostic factors for SCC of the temporal bone were evaluated regarding initial clinical symptoms and radiographic imaging. Methods:Clinical symptoms of the patients with primary SCC of the external auditor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 12 publications
1
45
0
Order By: Relevance
“…Reported 5-year overall survival rates for surgically treated patients with T4 tumors range from 17% to 40%. 2,[4][5][6][12][13][14] A meta-analysis of 752 patients with advanced (T3, T4) cancers of the temporal bone 15 reported that 5-year overall survival rates for patients who underwent surgery 6 RT, preoperative chemoradiotherapy (CRT) followed by surgery, definitive CRT, and surgery followed by postoperative CRT were 53.5%, 85.7%, 43.6%, and 0%, respectively. These results suggest that preoperative CRT may lead to improved survival of surgically treated patients and that the effectiveness of definitive CRT may be equivalent to that of surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Reported 5-year overall survival rates for surgically treated patients with T4 tumors range from 17% to 40%. 2,[4][5][6][12][13][14] A meta-analysis of 752 patients with advanced (T3, T4) cancers of the temporal bone 15 reported that 5-year overall survival rates for patients who underwent surgery 6 RT, preoperative chemoradiotherapy (CRT) followed by surgery, definitive CRT, and surgery followed by postoperative CRT were 53.5%, 85.7%, 43.6%, and 0%, respectively. These results suggest that preoperative CRT may lead to improved survival of surgically treated patients and that the effectiveness of definitive CRT may be equivalent to that of surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…The extant literature consists of numerous case series that have reported a wide range of survival data, reflecting differences in the underlying characteristics of cohorts drawn from various institutions. 1,6,[8][9][10][12][13][14][15]18,19,22,24,[30][31][32][33][34][35][36][37][38][39][40][41] Historical survival data can be most readily generalized to clinical practice if factors predictive of outcome can be identified. Several larger series have reported preliminary descriptions of factors influencing survival, based on univariate comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Most cohorts have been limited to squamous cell histology, and comprehensive outcomes analyses have been limited. 2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Further complicating analysis, there is no recognized American Joint Committee on Cancer (AJCC) or Union Internationale Contre le Cancer (UICC) staging system for tumors of the external auditory canal/temporal bone, with multiple systems having been proposed. 3,16,25,26 To date, the most widely used system is the University of Pittsburgh staging system, first described in 1990 by Arriaga and colleagues 25 and modified in 2000 by Moody et al 3 Other than Pittsburgh stage and surgical margin status, no other factors have been consistently demonstrated to be associated with outcome, and multivariable analyses of factors affecting outcome have not been reported.…”
mentioning
confidence: 99%
“…Radiotherapy (Table III) It is well known that the prognosis for patients with TBSCC treated with chemo-radiotherapy (CHT-RT) alone is unsatisfactory [27,32,45]. Only a very few studies found that RT alone produced results comparable with combined surgery and RT [5,67].…”
Section: Treatment: Non-surgical Approachesmentioning
confidence: 99%